Neurorobotics and how it can make advanced surgeries easier - Sarfaraz, Asma; Yaqoob, Uzair; Khemani, Lavina (International Journal Of Community Medicine And Public Health, 2017)
Neurorobotics is a combination of neurosciences and robotics that leads to build artificial intelligence and cognitive system. Neurorobotics is a recent innovation in the field of medicine particularly for surgeries which require minimally invasive procedures. It is a technology that has control system based on both the autonomous and central nervous system. Neurorobotics has done considerable advancement in surgeries, through its commendable properties such as refined precision, stability and dexterity. It can perform simple tasks such as grasping and fenestrating. This device is capable of performing finely controlled motions which the human hands cannot and therefore perform more delicate procedures like for lesions present in brain parenchyma. This device has one rigid endoscope and three robot arms that have employed to perform procedures in many cases. The procedures are usually performed through a small burr hole. The basic skills of robots are to detect and identify objects as well as processing language.